KONYA MEVLÂNÂ DERVİSH LODGE, RİTUAL HALL (SEMAHÂNE) PAİNTED DECORATİON AND PERİODİC ANALYSİS - Ali Fuat BAYSAL (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi, 2023)
When Bahâeddîn Veled and his family came to Konya in the area where the Mevlânâ lodge came to Konya, and after this date, some architectural structures began to form around the structure. After the death of Mevlânâ in this area and the tomb was built on this area, this place has gained a asitane identity. One of the structures added over time is the structure of the sema, which is the place where the Sama (sema) ritual is an important ritual of Mawlavi. Although there are different opinions about when the existing structure was built, the structure is thought to exist within the 15th century. The fact that the scripts and decorations in the domes and panding of the ritual hall (semahâne) have the characteristics of this period strengthens our idea. Existing decorations are the most important examples in terms of dating the period of the structure. We do not have any information about Nakkaş or Nakkaşs that performs the decoration. The ornaments that carry the traces of the style we call Bursa School are similar to the castles of Edirne Üç Şerefeli Mosque. This similarity shows that the people who design and apply the decorations of the structures have adopted the same style and also show that there is a style unity between the two structures. This is an important detail.